Optimization of Pulsed Laser Cladding for Reconditioning of Ni–Al–Bronze (NAB) Marine Propeller - Iatan, George Ciprian; Cuculea, Dan Cristian; Ardelean, George; Stanciu, Elena Manuela; Pascu, Alexandru (MDPI AG, 2025)
The materials used in the marine environment are generally selected for their high performances in aggressive operational media. This is also the case for marine propellers, which are mainly manufactured from cast nickel–aluminum bronze (NAB), due to their favorable mechanical properties and corrosion resistance. This study is focused on maximizing the efficiency of pulsed laser cladding through coaxial powder feeding, aiming to develop it as a sustainable reconditioning method for NAB propellers. A pulsed-wave laser (Trumpf TruPulse 556) and a cladding head (Precitec WC 50) were used for cladding of CuNi-alloyed powder on an NAB substrate. One of the main challenges was the high reflectivity of the copper matrix, present in both the base material of the propeller and in the powder, which significantly reduces laser energy absorption. However, good-quality cladded layers were obtained by optimizing the process cladding parameters. The coatings were characterized by optical and scanning electron microscopy. Microhardness values indicated transition regions within the coating layer. The results demonstrate that laser cladding with pulsed lasers is an effective and promising surface engineering method for reconditioning of damaged marine propellers. The obtained results create a path for future research aimed at extending the service life of copper-based marine components.
Keywords: laser cladding; nickel–aluminum bronze; marine propeller